Sosialisasi Pemberdayaan Anak Muda Untuk Mendorong Regenerasi Di Sektor Pertanian Distrik Walesi Kampung Apenas - Buni, Novi Laka; Vernanda, Vedrix (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The condition of young people in Papua's mountains, Walesi District, especially in Apenas Village, is that they are currently more involved in technology, they spend more time on social media, and spend a lot of time hanging out and drinking, they rarely help their parents work in the garden. So the sources of basic food ingredients in Papua are starting to decrease because those who work a lot and spend their time in the fields or gardens are older people (pace and mace) whose energy or strength is weak or unproductive (no longer strong). Socialization and assistance regarding the concept of empowering young people to encourage regeneration in the agricultural sector is very important to increase young people's awareness of how important the agricultural sector is in everyday life. This service activity aims to provide understanding to young children of the current generation about the importance of the agricultural sector. The implementation method is socialization where the concept is to deliver material and provide direct practice to young people in the location by planting strawberries which are local potential in the area. The output of the results of this activity is that young people's awareness is starting to emerge, namely about the factors causing the decline in agricultural production in the village due to the lack of more productive workers, therefore young people are needed whose workers are still productive in the agricultural sector to increase production results in the area. If you only rely on parents to manage the farm, their energy will be lacking so that agricultural results will be hampered, that is, the results will definitely decrease, therefore this service provides a solution for young people to realize that they are an asset for the agricultural sector in Apenas Village, Walesi District. Keywords: Sustainable Agriculture, Traditional Agriculture, Farmers, Sustainability